Surgical Practice in Resource‐Limited Settings: Perspectives of Medical Students and Early Career Doctors: A Narrative Review - BillSmith Anyinkeng Achanga; Christian Wabene Bisimwa; Victor Oluwafemi Femi‐Lawal; Nnoko Sona Akwo; Tohson Falake Toh (Health Science Reports)
ABSTRACT Introduction Surgical practices in low‐resource countries often fail to meet established standards. Both doctors and medical students have limited exposure to surgical cases, which hinders training and the development of surgical specialization. This study highlights the current state of surgical practice from a trainee's perspective, explores existing gaps in training and capacity building, and recommends practical solutions. Methods We conducted a literature search on PubMed, Google Scholar, and other scientific databases using search terms such as “surgical practice,” “doctors' perspectives in surgical practice,” “surgery in low‐ and middle‐income countries,” and “solutions to surgical inadequacy.” We included studies published from 2015 to 2024, with exceptions for a few highly relevant studies published prior to 2015. Results We outline the limitations identified in the literature concerning surgical training and healthcare in low‐ and middle‐income countries. Many centers lack adequate infrastructure, human resources, and training. These challenges negatively affect the skills and quality of surgical care. However, some centers demonstrate that surgical practice is feasible through collaboration with institutions established in higher‐income contexts. Conclusion Telesurgery, task shifting and sharing, high‐impact, low‐cost surgeries, and collaborations with more developed health systems could effectively bridge the gap in surgical availability in LMICs.